Timing of rapid weight gain and its effect on subsequent overweight or obesity in childhood: findings from a longitudinal birth cohort study - Yi-Fan Li; Shio-Jean Lin; Tung-liang Chiang (BMC, 2020)
Abstract Background Rapid weight gain (RWG) has been recognized as an important determinant of childhood obesity. This study aims to explore the RWG distribution among children at six-month intervals from birth to two years old and to examine the association of RWG in each interval with overweight or obesity development in preschool- and school-aged children. Methods Data were obtained from the Taiwan Birth Cohort Study, which is a nationally representative sample of 24,200 children who participated in a face-to-face survey. A total of 17,002 children had complete data both for weight and height at each of the five measurement time periods. Multivariable logistic regression models quantified the relationship between RWG and childhood overweight or obesity. Results A total of 17.5% of children experienced rapid weight gain in the first six months of age, compared to only 1.8% of children from 18-24 months. RWG was significantly associated with an increased risk of developing overweight or obesity at 36 months (RWG birth-6 months: OR = 2.6, 95% CI: 2.3-2.8; RWG 18-24 months: OR = 3.7, 95% CI: 2.9-4.6), 66 months (RWG birth-6 months: OR = 2.2, 95% CI: 2.0-2.4; RWG 18-24 months: OR = 2.3, 95% CI: 1.8-2.8), and 8 years of age (RWG birth-6 months: OR = 1.7, 95% CI: 1.6-1.9; RWG 18-24 months: OR = 2.4, 95% CI: 2.0-3.0). Conclusions Childhood RWG increased the risk of subsequent overweight or obesity, regardless of the specific time interval at which RWG occurred before the age of two years. The results reinforce the importance of monitoring childhood RWG continuously and show the risks of childhood RWG with respect to the development of overweight or obesity at preschool and school ages.